Digest: Hypothesis testing in biogeography using phylogenetic trees*. (3rd November 2020) - Miller, Elizabeth Christina
Abstract: How can we test whether biogeographic dispersal rates coincide with geologic events? Hua and Bromham developed a model‐based approach to generate a null distribution of colonization times under constant dispersal rates, overcoming a problem related to the geometry of phylogenetic trees.